Odpowiedź :
Odpowiedź:
A 3x-y=5
1,5x+0,5y=-2,5
-------
-y=5-3x / * -1
1,5x+0,5y= - 2,5
-------
y=3x-5 podst.
1,5x+0,5 (3x-5) = -2,5
1,5x +1,5x- 2,5 = -2,5
3x=0
x=0 a y = 3*0-5=-5
B 5x-3y=-2
7x+7y=14
-----
5x=-2 +3y/5
7x+7y=14
------
x= -2/5 + 3/5 y podst.
7(-2/5 + 3/5y) +7y =14
-2,8+4,2y+7y=14
11,2y=16,8/11,2
y=1,5 i x= -2/5+ 3/5*1,5= -2,5+0,9= - 1,6
c
6x=3-5y/6
18x+7y=17
-----
x=3/6 - 5/6 y
18x+7y=17 podst
18(0,5 - 5/6y) +7y= 17
9-15y+7y=17
-8y=10
y= -0,8
d
4x=5y+2
2x+7y=1
-----
4x=5y+2 / 4
2x+7y=1
-------
x=1,25y+0,5 podst
2(1,25y+0,5) + 7y=1
2,5y+1 +7y = 1
9,5 y = 0
y=0 i x= 1,25 *0 +0,5 =0,5
e
2y=6x-5/2
3x+2y=4
---
y=3x-5/2
podst
3x+2(3x-5/2)=4
3x+6x-5=4
9x=9/9
x=1 i y= 3*1 - 2,5=0,5
Szczegółowe wyjaśnienie:
i F
14x+3y=4
2x-6=5y
14x+3y=4
2x=5y+6/2
14x+3y=4
x=2,5y+3 podst
14(2,5y+3)+3y=4
35y+42+3y=4
38y=-38/ 38
y = -1 i x= 2,5 * (-1)+3=0,5